Computer-Delivered Cognitive Training and Transcranial Direct Current Stimulation in Patients With HIV-Associated Neurocognitive Disorder: A Randomized Trial - Ownby, Raymond L.; Kim, Jae (Frontiers in Aging Neuroscience, 2021)
Objective: HIV infection is associated with impaired cognition, and as individuals grow older, they may also experience age-related changes in mental abilities. Previous studies have shown that computer-based cognitive training (CCT) and transcranial direct current stimulation (tDCS) may be useful in improving cognition in older persons. This study evaluated the acceptability of CCT and tDCS to older adults with HIV-associated neurocognitive disorder, and assessed their impact on reaction time, attention, and psychomotor speed. Methods: In a single-blind randomized study, 46 individuals with HIV-associated mild neurocognitive disorder completed neuropsychological assessments and six 20-min training sessions to which they had been randomly assigned to one of the following conditions: (1) CCT with active tDCS; (2) CCT with sham tDCS, or (3) watching educational videos with sham tDCS. Immediately after training and again 1 month later, participants completed follow-up assessments. Outcomes were evaluated via repeated measures mixed effects models. Results: Participant ratings of the intervention were positive. Effects on reaction time were not significant, but measures of attention and psychomotor speed suggested positive effects of the intervention. Conclusion: Both CCT and tDCS were highly acceptable to older persons with HIV infection. CCT and tDCS may improve cognitive in affected individuals. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [NCT03440840].